Optimal current setpoint computation for externally excited synchronous machines - Reinhard, Johannes; Löhe, Klaus; Graichen, Knut (6th IEEE Conference on Control Technology and Applications (CCTA), 2022)

Road quality estimation by autoregressive filtering for a two-axle vehicle - Löhe, Klaus; Zehelein, Thomas; Roppenecker, Günter (At-Automatisierungstechnik, 2016)
This article introduces a concept for road quality estimation by autoregressive filtering for a two-axle vehicle. A Kalman-Filter is used for observing the road state. The unevenness power spectrum density of the road is calculated by autoregressive filtering. Therefore the road qualitiy can be found. Using this information in the Kalman-Filter adapts it to the actual road and improves the estimation quality. The concept is run on a quarter-car test rig. Experimental results are shown.
Keywords: autoregressive filtering; Kalman-Filter; quarter-car test rig; Road quality estimation; two-axle vehicle